A novel method for analyzing the driving force of the bi-directional pig based on the four-element model. (April 2021) - Liu, Chang; Cao, Yuguang; Tian, Hongjun; Ma, Shuai
Abstract: The sufficient driving force is vital for ensuring the operational efficiency of the bi-directional pig. This paper carried out the high-velocity traction experiments by a custom-built experimental device to investigate the driving force of the bi-directional pig which experiences four stages during the running process. The four-element model (Burgers-Frenkel model) was rearranged for explaining the deformation and force condition of the sealing disc in each stage, and then a novel method for analyzing the driving force of the bi-directional pig was first proposed by using a dynamic analytical model which established based on the rearranged four-element model (hereinafter, the four-element model). The friction coefficient was determined with the method of combining the 3D numerical simulation and the experiment, and the model parameters were further extrapolated according to the experimental results. Our results indicate that the proposed analytical dynamic model has satisfying accuracy for predicting the driving force of the bi-directional pigs. The research results of this work are beneficial for avoiding the blockage accident and optimizing the pig design. Highlights: The four-element model was rearranged for explaining the variation of the driving force of the bi-directional pig. A dynamic analytical model of the bi-directional pig was established based on the rearranged four-element model. The velocity has an obvious effect on the driving force of the bi-directional pig, especially in the launching process.